Рационализация режима труда и отдыха в пошивочных цехах швейного производства: [обзор] / А. П. Кацева, Е. Ф. Занко - Кацева Алла Петровна (1972)
Экземпляры: ТО (20190415) / Инвентарный номер: 551033 / Сис.шифр: 687 / Авт.знак: К30 / ГРНТИ: 64 / ББК: 37